The Wiley Blackwell companion to wisdom literature - Adams, Samuel L.; Goff, Matthew J. (The Wiley Blackwell companions to religion, 2020)
"This handbook is designed to give the reader, whether an advanced scholar or an undergraduate student, a basic introduction to and overview of wisdom literature. The volume will also provide an impression of how this material has been read and interpreted in various contexts and historical periods. The authors engage the topic from a variety of approaches, asking historical, literary, theological, and feminist questions (among others) about wisdom literature. The essays offer detailed and thorough studies of the relevant texts and also discuss a number of issues that are pertinent to the study of wisdom literature, such as the figure of Solomon, pedagogy in the ancient world, and the oral transmission of sayings. While many of the essays focus on antiquity and the context in which wisdom literature was produced, the contributors deal with later periods as well, including our own context, as in, for example, the essay by Rindge on sapiential themes in contemporary cinema. The cultural contexts that the contributors take into consideration include both the ancient world, as in the essays by Adams and Samet on, respectively, Egypt and Mesopotamia, and also settings that are traditionally not prominent in the study of wisdom literature, such as the essay by Masenya, which compares the book of Proverbs to didactic and gnomic traditions in Africa"--